«Lectures are to be read ...» (to the organization A. Stronina public readings in Poltava) (Pedagogy of Higher and Secondary Education, 2014)
Pilipenko V. V. «Lectures are to be read ...» (to the organization A. Stronina public readings in Poltava).The article about A. Stronin`s educational activity in the field of public lectures. Author is substantiated pedagogical, organizational and management teachers ability as public lectures founder. Attention is accented on that A. Stronin considered the public lectures as holistic and original project of out of School Educational.
Keywords: A. Stronin; Sunday school; women’s gymnasium; education; public lectures